2011
DOI: 10.1158/1078-0432.ccr-10-1030
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide–Donating Acetylsalicylic Acid Induces Apoptosis in Chronic Lymphocytic Leukemia Cells and Shows Strong Antitumor Efficacy In vivo

Abstract: Purpose: Nitric oxide-donating acetylsalicylic acid (NO-ASA) has been shown to possess an antineoplastic effect in Wnt-/b-catenin-active cancers. As chronic lymphocytic leukemia (CLL) cells exhibit aberrantly active Wnt signaling, we investigated the effect of the para-isomer of NO-ASA on CLL cell survival in vitro and in a CLL-like xenograft mouse model.Experimental Design: Apoptosis in primary CLL cells was determined by flow cytometric annexin V-FITC (fluorescein isothiocyanate)/PI (propidium iodide) staini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
2
11
0
1
Order By: Relevance
“…Furthermore, the Wnt/b-catenin/TCF/Lef-1 signaling pathway is aberrantly active [Lu et al 2004] and its therapeutic inhibition has been demonstrated to induce apoptosis in primary CLL cells in vitro and reduce tumor growth in a xenograft mouse model [Gandhirajan et al 2010]. We have recently demonstrated, confirming data obtained in solid tumors, that para-NO-ASA potently induced apoptosis in vitro in primary CLL cells and prevented tumor growth in a xenograft CLL-like mouse model [Razavi et al 2011]. Also here b-catenin cleavage was involved in apoptotic cell death.…”
Section: Introductionsupporting
confidence: 82%
“…Furthermore, the Wnt/b-catenin/TCF/Lef-1 signaling pathway is aberrantly active [Lu et al 2004] and its therapeutic inhibition has been demonstrated to induce apoptosis in primary CLL cells in vitro and reduce tumor growth in a xenograft mouse model [Gandhirajan et al 2010]. We have recently demonstrated, confirming data obtained in solid tumors, that para-NO-ASA potently induced apoptosis in vitro in primary CLL cells and prevented tumor growth in a xenograft CLL-like mouse model [Razavi et al 2011]. Also here b-catenin cleavage was involved in apoptotic cell death.…”
Section: Introductionsupporting
confidence: 82%
“…3 and 4). The induction of cleavage of the apoptotic proteins caspase 3, caspase 9 and PARP has been linked to blockade of Wnt/β-catenin signaling and provides further evidence that promotion of apoptosis by PG545 was being driven by Wnt inhibition [28-31]. The contrasting effects of PG545 on β-catenin in our AsPC-1 xenograft model compared to the mPDAC genetic model described by Ostapoff and colleagues may suggest differences in β-catenin regulation between human and mouse pancreatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Four chiral N-acetylalaninate ester prodrugs (see Figure  3) were evaluated in this study based on: (1) our previous experimental observations showing that OPH has specificity towards α-naphthyl-N-acetylalaninate substrates [24]; (2) in silico protein-ligand binding studies suggesting that S-NPAA has a reasonable affinity to the active site found in predicted three dimensional models of rat and human OPH [23]; (3) structural similarity to NO-ASA which has a toxicology profile superior to that of aspirin [18]. Our first objective was to determine whether the hydrolysis of the newly designed prodrugs was catalyzed, and thus activated, by OPH.…”
Section: Resultsmentioning
confidence: 99%
“…S-NPAA was found to deplete GSH in a manner completely analogous to that of NO-ASA, a well-characterized anti-cancer drug with minimal in vivo toxicity [18]. NO-ASA exerts an anticancer effect by depleting intracellular GSH and causing oxidative stress induced apoptosis by activation of the intrinsic death pathway [15].…”
Section: Discussionmentioning
confidence: 99%